Aortic Cross-Sectional Area/Height Ratio and Outcomes in Patients With a Trileaflet Aortic Valve and a Dilated Aorta. Issue 22 (29th November 2016) - Masri, Ahmad; Kalahasti, Vidyasagar; Svensson, Lars G.; Roselli, Eric E.; Johnston, Douglas; Hammer, Donald; Schoenhagen, Paul; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background: In patients with a dilated proximal ascending aorta and trileaflet aortic valve, we aimed to assess (1) factors independently associated with increased long-term mortality and (2) the incremental prognostic utility of indexing aortic root to patient height. Methods: We studied consecutive patients with a dilated aortic root (≥4 cm) that underwent echocardiography and gated contrast-enhanced thoracic aortic computed tomography or magnetic resonance angiography between 2003 and 2007. A ratio of aortic root area over height was calculated (cm 2 /m) on tomography, and a cutoff of 10 cm 2 /m was chosen as abnormal, on the basis of previous reports. All-cause death was recorded. Results: The cohort comprised 771 patients (63 years [interquartile range, 53–71], 87% men, 85% hypertension, 51% hyperlipidemia, 56% smokers). Inherited aortopathies, moderate to severe aortic regurgitation, and severe aortic stenosis were seen in 7%, 18%, and 2%, whereas 91% and 54% were on β-blockers and angiotensin-converting enzyme inhibitors, respectively. Aortic root area/height ratio was ≥10 cm 2 /m in 24%. The Society of Thoracic Surgeons score and right ventricular systolic pressure were 3.3±3 and 31±7 mm Hg, respectively. At 7.8 years (interquartile range, 6.6–8.9), 280 (36%) patients underwent aortic surgery (76% within 1 year) and 130 (17%) died (1% in-hospital postoperative mortality). A lower proportion of patients in the surgical (versus nonsurgical) group died (13% versus 19%, P <0.01). On multivariable Cox proportional hazard analysis, aortic root area/height ratio (hazard ratio, 4.04; 95% confidence interval [CI], 2.69–6.231) was associated with death, whereas aortic surgery (hazard ratio, 0.47; 95% CI, 0.27–0.81) was associated with improved survival (both P <0.01). For longer-term mortality, the addition of aortic root area/height ratio ≥10 cm 2 /m to a clinical model (Society of Thoracic Surgeons score, inherited aortopathies, hypertension, hyperlipidemia, medications, aortic regurgitation, and right ventricular systolic pressure), increased the c-statistic from 0.57 (95% CI, 0.35–0.77) to 0.65 (95% CI, 0.52–0.73) and net reclassification index from 0.17 (95% CI, 0.02–0.31) to 0.23 (95% CI, 0.04–0.34), both P <0.01. Of the 327 patients with aortic root diameter between 4.5 and 5.5 cm, 44% had an abnormal aortic root area/height ratio, of which 78% died. Conclusions: In patients with dilated aortic root and trileaflet aortic valve, a ratio of aortic root area to height provides independent and improved stratification for prediction of death. Abstract : Supplemental Digital Content is available in the text.